2001
DOI: 10.1557/proc-692-h6.30.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiative recombination processes of thermal donors in silicon

Abstract: There is a recent, renewed attention on the possible development of optical emitters compatible with silicon microelectronic technology and it has been recently shown that light emitting diodes could be manufactured on dislocated silicon, where dislocations were generated by plastic deformation or ion implantation. Among other potential sources of room temperature light emission, compatible with standard silicon-based ULSI technology, we have studied old thermal donors (OTD), as the origin of their luminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In order to evaluate the relative influence of these two traps on the recombination processes, and thus on the lifetime, we have compared in figure 5 the evolution with the annealing time of the lifetime and of the reciprocal of the intensity of the P line at 0.767 eV, which is always present in the PL spectra (see figure 6) in the presence of thermal donors [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to evaluate the relative influence of these two traps on the recombination processes, and thus on the lifetime, we have compared in figure 5 the evolution with the annealing time of the lifetime and of the reciprocal of the intensity of the P line at 0.767 eV, which is always present in the PL spectra (see figure 6) in the presence of thermal donors [12].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the parameters of the deep levels associated with majority carrier traps were obtained from the results of our previous work [12], where standard DLTS and minority carrier transient spectroscopy (MCTS) measurements were carried out by means of a SULA Tech. Inc. instrumentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that we have already shown that the intensity dependence of the P line on the treatment time follows that of the NL8 center [15][16][17][18] we might conclude that the concentration of this center is not affected by the applied pressure, while that of the other donors is. Considering that we have already shown that the intensity dependence of the P line on the treatment time follows that of the NL8 center [15][16][17][18] we might conclude that the concentration of this center is not affected by the applied pressure, while that of the other donors is.…”
Section: A Samples Heat Treated At 450°cmentioning
confidence: 86%
“…The overall concentration of these donors, which depends on the temperature, on the annealing time, and on the initial oxygen content, as well as on their double donor nature, could be determined by Hall effect measurements. 15,16 For this reason, we consider the presence of the P line in the PL spectrum as the fingerprint of a specific center generated during the thermal annealing at 450°C, which is, in fact, present in all the samples examined, as it shown in Fig. For one of these donor centres, the NL8 one, whose electronic structure is known from electron paramagnetic resonance and electron-nuclear double resonance measurements, 14 a correlation was found between the PL intensity in the excitonic range and the intensity of a PL line at 0.767 eV, known as the P line and the annealing time at 450°C.…”
Section: A Samples Heat Treated At 450°cmentioning
confidence: 99%